What do we know about the future of agrobiodiversity in relation to food systems? - Cenacchi, Nicola; Gotor, Elisabetta; Petsakos, Athanasios; Schiek, Benjamin (CGIAR System Organization, 2022)
Key messages - Agrobiodiversity (or agricultural biodiversity) refers to the diversity of living organisms (plants, animals, bacteria, etc.) that underpin agricultural systems (Wood & Lenne’, 1999). It provides numerous critical beneﬁts, from on-farm crop diversity and genetic resources that allow farmers to adapt crops to changing environments (Fowler & Hodgkin, 2004), to the provision of ecosystem services such as pollination, disease and pest resistance, soil health, and water conservation (Hajjar et al., 2008). These benefits in turn support resilient livelihoods, food security (Waha et al., 2022), and diversiﬁed, nutritious diets (Love & Spaner, 2007). - A number of ex ante theoretical and practical approaches have been used to show how greater agricultural biodiversity is connected to higher production and lower risk exposure, and assess the role that agrobiodiversity plays in supporting resilience of agricultural systems (Di Falco, 2012; Di Falco & Chavas, 2009). But little has been done to integrate the measurement of agrobiodiversity per se into foresight modeling, or to apply foresight tools and methods to study long-term effects of agrobiodiversity on a range of socioeconomic or environmental outcomes. - The recent development of the Agrobiodiversity Index and advances in integrated modeling systems provide opportunities for improved scenario analysis focused on agrobiodiversity and informed by agroecology and agricultural economics theory.